(untitled) (Research, Society and Development, 2023)
Chronic kidney disease in individuals on hemodialysis promotes several metabolic changes. Correct dietary therapy guidance aims to control water-electrolyte disorders and nutritional deficiencies, as well as avoiding malnutrition, which is very common in this population. In view of the problems related to this disease, the objective of this bibliographic review was to collect, from scientific publications, the main nutritional recommendations for patients with CKD undergoing hemodialysis. This integrative review was structured based on the selection of 23 scientific articles, published in English and Portuguese and obtained through the following databases: SciELo – Brasil, Google Scholar, Mendeley, CAPS Periódicos and Acervo+ Index Base. Chronic kidney disease imposes on the patient several metabolic changes induced by functional impairment of the kidneys. Within this context, parameters such as phosphorus, potassium, sodium, vitamin D, water intake and protein consumption must be closely monitored. Healthy eating before, during and after hemodialysis sessions is essential to prevent malnutrition and improve the response to hemodialysis treatment. Planned dietary therapy and monitoring by a professional nutritionist reduce uremic symptoms, correct nutritional deficiencies and provide support for improving the patient’s general condition.